Multi-faceted role of LRP1 in the immune system - Sizova, Olga; John, Lisa St.; Ma, Qing; Molldrem, Jeffrey J. (Frontiers in Immunology, 2023)
Graft versus host disease (GVHD) represents the major complication after allogeneic hematopoietic stem cell transplantation (Allo-SCT). GVHD-prone patients rely on GVHD prophylaxis (e.g. methotrexate) and generalized anti-GVHD medical regimen (glucocorticoids) (1). New anti-GVHD therapy strategies are being constantly explored, however there is an urgent need to improve current treatment, since GVHD-related mortality reaches 22% within 5 years in patients with chronic GVHD (2). This review is an attempt to describe a very well-known receptor in lipoprotein studies – the low-density lipoprotein receptor related protein 1 (LRP1) - in a new light, as a potential therapeutic target for GVHD prevention and treatment. Our preliminary studies demonstrated that LRP1 deletion in donor murine T cells results in significantly lower GVHD-related mortality in recipient mice with MHC (major histocompatibility complex) -mismatched HSCT (3). Given the importance of T cells in the development of GVHD, there is a significant gap in scientific literature regarding LRP1’s role in T cell biology. Furthermore, there is limited research interest and publications on this classical receptor molecule in other immune cell types. Herein, we endeavor to summarize existing knowledge about LRP1’s role in various immune cells to demonstrate the possibility of this receptor to serve as a novel target for anti-GVHD treatment.